PENDAMPINGAN PERHITUNGAN HARGA POKOK PRODUKSI TANAMAN BUDIDAYA KELOMPOK MASYARAKAT TANI - Susilowati, Retno Yuni Nur; Amelia, Yunia; Alvia, Liza; Eka Putri, Widya Rizki (Faculty of Economics and Business Lampung University, 2023)
This community service activity aims as follows. First, increase the insight and knowledge of target partner communities regarding good financial and accounting governance in managing their agriculture. Second, increase the knowledge and skills of the target partner community regarding the calculation of the cost of production. Third, increase the knowledge and skills of the target partner community in making financial reports. Fourth, increase the knowledge of target partner communities about legal capital sources and the requirements for obtaining them. Fifth, increase the knowledge and skills of target partner communities regarding management and marketing. The results of this service are in the form of knowledge and insight as provisions for farming communities to calculate the cost of production and financial literacy